Urinary and Plasma Catecholamines and Metanephrines in Dogs with Pheochromocytoma, Hypercortisolism, Nonadrenal Disease and in Healthy Dogs. (March 2015) - Salesov, E.; Boretti, F.S.; Sieber‐Ruckstuhl, N.S.; Rentsch, K.M.; Riond, B.; Hofmann‐Lehmann, R.; Kircher, P.R.; Grouzmann, E.; Reusch, C.E.
Abstract : Background: Diagnosis of pheochromocytoma (PC) is based on a combination of clinical suspicion, finding an adrenal mass, increased plasma, and urine concentrations of catecholamine metabolites and is finally confirmed with histopathology. In human medicine, it is controversial whether biochemically testing plasma is superior to testing urine. Objectives: To measure urinary and plasma catecholamines and metanephrines in healthy dogs, dogs with PC, hypercortisolism (HC), and nonadrenal diseases (NAD) and to determine the test with the best diagnostic performance for dogs with PC. Animals: Seven PC dogs, 10 dogs with HC, 14 dogs with NAD, 10 healthy dogs. Methods: Prospective diagnostic clinical study. Urine and heparin plasma samples were collected and stored at −80°C before analysis using high‐pressure liquid chromatography (HPLC) coupled to electrochemical detection or tandem mass spectrometry were performed. Urinary variables were expressed as ratios to urinary creatinine concentration. Results: Dogs with PC had significantly higher urinary normetanephrine and metanephrine : creatinine ratios and significantly higher plasma‐total and free normetanephrine and plasma‐free metanephrine concentrations compared to the 3 other groups. There were no overlapping results of urinary normetanephrine concentrations between PC and all other groups, and only one PC dog with a plasma normetanephrine concentration in the range of the dogs with HC and NAD disease. Performances of total and free plasma variables were similar. Overlap of epinephrine and norepinephrine results between the groups was large with both urine and plasma. Conclusion and clinical importance: Measurement of normetanephrine is the preferred biochemical test for PC and urine was superior to plasma.